Relacije situaciono - motoricke koordinacije i takmicarske uspesnosti gimnasticarki - Petkovic, E. (Facta Universitatis: Series Physical Education and Sport, 2004)
On a sample consisting of 58 gymnasts, ages 7 through 9, from 8 cities in Serbia & Montenegro, a set of 10 predictor variables was applied for the purpose of evaluating situational-motor coordination, along with a set of 5 criterion variables for the purpose of evaluating the female gymnasts' competitive success. By means of the canonical-corelational analysis the relations between situational-motor coordination and competitive success in sports gymnastics were determined. The relations were presented by means of two significant factors. The two-dimensional structure of the situational-motor coordination indicates that the first factor is responsible for the execution speed of complex motor tasks, and the second for rhythmic coordination, the correct performance of hand motions on the sagittal and frontal plains, determined by set angles. Within the two-dimensional structure of the competitive success of gymnasts, it is possible to meaningfully interpret the second factor which is responsible for overall success, as it is significantly defined by all the variables used for evaluating short routines on individual pieces of apparatus (Vaults, Parallel bars, Balance beams, and Floor exercises) and the all-around competition.